2021
DOI: 10.1038/s41598-021-81641-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA EBLN3P promotes the progression of osteosarcoma through modifying the miR-224-5p/Rab10 signaling axis

Abstract: The treatment of patients with advanced-stage osteosarcoma represents a major challenge, with very few treatments currently approved. Although accumulating evidence has demonstrated the importance of lncRNAs in osteosarcoma, the current knowledge on the functional roles and molecular mechanisms of lncRNA endogenous born avirus-like nucleoprotein (EBLN3P) is limited. At present, the expressions of EBLN3P and miR-224-5p in osteosarcoma tissues were quantified by reverse transcription-quantitative PCR assay, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Similarly, EBLN3P promotes the recovery of impaired spiral ganglion neurons by competitively binding miR-204-5p, regulating TMPRSS3 expression [78]. Despite showing a regulatory function in different cancer types [79,80], here we demonstrated a coding capacity of EBLN3P in hASC, which represents a possible dual-function of this transcript in stem cell biology, including a putative secreted smORF-derived microprotein.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, EBLN3P promotes the recovery of impaired spiral ganglion neurons by competitively binding miR-204-5p, regulating TMPRSS3 expression [78]. Despite showing a regulatory function in different cancer types [79,80], here we demonstrated a coding capacity of EBLN3P in hASC, which represents a possible dual-function of this transcript in stem cell biology, including a putative secreted smORF-derived microprotein.…”
Section: Discussionmentioning
confidence: 64%
“…Xu et al reported that EBLN3P regulates UHMK1 expression by targeting miR-323a-3p/UHMK1 and accelerates colorectal cancer progression (30). Dai et al demonstrated that EBLN3P accelerates the progression of osteosarcoma by regulating miR-224-5p/Rab10 and is a novel biomarker for the diagnosis and treatment of osteosarcoma (31). However, a literature search showed a limited number of studies reporting the biological mechanisms whereby the remaining pMRlncRNAs affect diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, based on the miRNA-lncRNA-mRNA co-expression relationship, we discovered that EBLN3P and miR-204-5p strongly correlated with EpCAM were potential to be prognostic biomarkers and therapeutic targets in PCa. Some studies have demonstrated that EBLN3P promotes the progression of liver cancer via alteration of microRNA-144-3p/DOCK4 pathway, and osteosarcoma through modifying the miR-224-5p/Rab10 signaling axis ( Li et al, 2020b ; Dai et al, 2021 ). Unfortunately, no research explores the correlation between prostate cancer and EBLN3P.…”
Section: Discussionmentioning
confidence: 99%